Regional Insights: A selection of articles providing a fresh take on regional studies: What EU territory do we want to hand over to the next generations?. Issue 4 (June 2019) - Mehlbye, Peter; Böhme, Kai; Martin, Derek; Schön, Peter
No abstract available